Directed optimization of a newly identified squalene synthase from Mortierella alpine based on sequence truncation and site-directed mutagenesis. (1st October 2015) - Huang, Di; Yao, Yongpeng; Zhang, Hang; Mei, Zhu; Wang, Ru; Feng, Lu; Liu, Bin
Abstract: Terpenoids, a class of isoprenoids usually isolated from plants, are always used as commercial flavor and anticancer drugs. As a key precursor for triterpenes and sterols, biosynthesis of squalene (SQ) can be catalyzed by squalene synthase (SQS) from two farnesyl diphosphate molecules. In this work, the key SQS gene involved in sterols synthesis by Mortierella alpine, an industrial strain often used to produce unsaturated fatty acid such as γ-linolenic acid and arachidonic acid, was identified and characterized. Bioinformatic analysis indicated that MaSQS contained 416 amino acid residues involved in four highly conserved regions. Phylogenetic analysis revealed the closest relationship of MaSQS with Ganoderma lucidum and Aspergillus, which also belonged to the member of the fungus. Subsequently, the recombinant protein was expressed in Escherichia coli BL21(DE3) and detected by SDS-PAGE. To improve the expression and solubility of protein, 17 or 27 amino acids in the C-terminal were deleted. In vitro activity investigation based on gas chromatography–mass spectrometry revealed that both the truncated enzymes could functionally catalyze the reaction from FPP to SQ and the enzymatic activity was optimal at 37 °C, pH 7.2. Moreover, based on the site-directed mutagenesis, the mutant enzyme mMaSQSΔC17 (E186K) displayed a 3.4-fold improvement in catalytic efficiency ( k  cat / K  m ) compared to the control. It was the first report of characterization and modification of SQS from M. alpine, which facilitated the investigation of isoprenoid biosynthesis in the fungus. The engineered mMaSQSΔC17 (E186K) can be a potential candidate of the terpenes and steroids synthesis employed for synthetic biology.